Asean-5 Cluster Report : Evolution of Monetary Policy Frameworks. (IMF Staff Country Reports; Country Report ;, 2016)
This paper examines the evolution of monetary policy frameworks of the Association of Southeast Asian Nations (ASEAN)-5 economies, with particular focus on changes since the Asian financial crisis and the more recent period of unconventional monetary policies in advanced economies. Monetary policy frameworks of the ASEAN-5 economies have on the whole performed well since the crisis, delivering both price and financial stability during a period of significant domestic and regional transformation and global macroeconomic and financial turmoil. Not surprisingly, therefore, successful outcomes in most cases entailed significant changes to operating frameworks and refinement of policy objectives.